And still we rise : the trials and triumphs of twelve gifted inner-city students - Corwin, Miles (New York : Perennial, 2001)
Bestselling author of "The Killing Season" and veteran "Los Angeles Times" reporter Miles Corwin spent a school year with twelve high school seniors -- South-Central kids who qualified for a gifted program because of their exceptional IQs and test scores. Sitting alongside them in classrooms where bullets were known to rip through windows, Corwin chronicled their amazing odyssey as they faced the greatest challenges of their academic lives. "And Still We Rise" is an unforgettable story of transcending obstacles that would dash the hopes of any but the most exceptional spirits.
Introduction -- Prologue: Olivia: I don't want her -- September: Sadikifu: Tell me why -- Toya: I never dreamed I would see sixteen -- Olivia: My only safe haven -- Venola: My rainbow is waiting for me -- Miesha: My talent is perseverance -- Mama Moultrie: I touch lives -- Fall: Toni Little: Learn to compete -- Sabreen: One less child to support -- Affirmative action: To treat some persons equally, we must treat them differently -- Sabreen: Doll and a teddy bear -- Latisha: Stolen childhood -- Olivia: Easy money -- South-central: Sunlit ghetto -- Claudia: Sacrifice and pressure -- Curt: Stanford -- Mama Moultrie: Our best hope -- Olivia: Legal limbo -- Toni Little: Ride of their lives -- Second semeste: Willie: Wishing it was just a dream -- Naila: All-American -- Olivia: Sentencing -- Toya: I'm really here -- Danielle: Education before athletics -- Princess: Happy ending -- Toni Little: Brink of madness -- Spring: Olivia: Locked up -- Scott Braxton: Drained -- Yvonne Noble: Reading is fundamental -- Mama Moultrie: Can I get an Amen? -- Fourth substitute: It's harder than it looks -- Affirmative action: Equality as a result -- Toni Little: I could use a little more time -- Exam: Where the rubber meets the road -- Scott Allen: Different approach -- Mama Moultrie: Some free advice -- Graduation: Still we rise -- Epilogue -- Afterword -- Acknowledgments -- Notes.
Includes bibliographical references.
Keywords: Gifted children -- Education (Secondary) -- United States -- Case studies; Children with social disabilities -- Education (Secondary) -- United States -- Case studies; Education, Urban -- United States -- Case studies; Crenshaw High School (Los Angeles, Calif.)